Square contour algorithm for blind equalization of QAM signals - Trasapong Thaiupathump (2018)
A new algorithm for blind equalization is introduced. The square contour algorithm (SCA) minimizes dispersion of equalizer output from a square. The SCA combines the advantages of the generalized Sato algorithm (GSA) and the constant modulus algorithm (CMA). It includes phase recovery and offers good convergence characteristics. By adding a constellation-matched error (CME) term to the cost function of the SCA, a modified SCA (MSCA) is obtained. The MSCA improves equalizer convergence performance. Simulations and analysis demonstrate the good performance of the proposed algorithms. © 2006 Elsevier B.V. All rights reserved.